Analisis Perbedaan Kinerja Keuangan Berdasarkan Return on Asset (ROA) Antar Industri Perbankan, Makanan dan Minuman, serta Telekomunikasi Menggunakan One-Way Anova - Dea Aprilia; Rahma Irvia; Fazrianisa Fazrianisa; Sunita Dasman (GLOBAL SCIENTS PUBLISHER, 2026)
The main goal of this study is to evaluate the variations in Return on Assets (ROA) in the banking, telecommunications, and food and beverage industries on the IDX for the period 2021–2025. Using the One-Way ANOVA and Welch Test methods, this study analyzed 45 observations from nine sample companies. Descriptive statistics results show that the food and beverage industry has the highest average ROA at 10.31%, followed by the telecommunications industry at 6.01%, and the banking industry at 3.43%. With a p-value of 0.000 from the Welch Test (Sig. < 0.05), this study empirically proves a very real gap in average ROA between industry sectors. The Welch test results show a significance value of 0.000, indicating a significant difference in average ROA across industries. The follow-up Games-Howell test showed that the food and beverage industry has a significantly different average ROA compared to the banking and telecommunications industries, while no significant difference in average ROA was found between the banking and telecommunications industries. This study concludes that differences in operational characteristics and asset management in each industry affect the level of company profitability, as reflected in Return on Assets (ROA).